Peramalan Kunjungan Pasien di Balai Kesehatan Menggunakan Metode Time Series dengan Interpretasi Analisis SWOT - Basri, I (Jurnal Teknologi dan Informasi (JATI), 2020)
Various outbreaks of disease currently encourage increased public awareness of health this can affect the surge in patient visits at the health center if the public wants to seek treatment there, for that health center must have readiness in fulfilling facilities and support services, in this case the health center must do careful planning activities one of them with forecasting activities (Forecasting) to find out patient visits that will come This study did forecasting using Trend Analysis and Holt-Winters methods that are suitable for processing time series data, then to the second this method will compare which one is the best. The final result shows the MAPE value of each method, namely Trend Analysis; 8.70% and Holt-Winters; 7.90% for forecasting 2 years in the future. It can be said that the smallest error value is Holt-Winter, from the patient visit data with MAPE 7.90% which is said to be a very good forecasting category by producing a total value of Forecast = 53894.2 with an average monthly = 2245.59 this monthly result is used the reference to the number of visitors who come for each month is around 2245 people. after that a combination of SWOT Analysis is done to develop the strategy going forward by looking at the shortcomings and opportunities that will occur.